PlantNLRatlas: a comprehensive dataset of full- and partial-length NLR resistance genes across 100 chromosome-level plant genomes - Li, Xiang; Ma, Linna; Wang, Yingmin; Ye, Chen; Guo, Cunwu; Li, Yingbin; Mei, Xinyue; Du, Fei; Huang, Huichuan (Frontiers in Plant Science, 2023)
Plants have evolved two layers of protection against biotic stress: PAMP-triggered immunity (PTI) and effector-triggered immunity (ETI). The primary mechanism of ETI involves nucleotide-binding leucine-rich repeat immune receptors (NLRs). Although NLR genes have been studied in several plant species, a comprehensive database of NLRs across a diverse array of species is still lacking. Here, we present a thorough analysis of NLR genes across 100 high-quality plant genomes (PlantNLRatlas). The PlantNLRatlas includes a total of 68,452 NLRs, of which 3,689 are full-length and 64,763 are partial-length NLRs. The majority of NLR groups were phyletically clustered. In addition, the domain sequences were found to be highly conserved within each NLR group. Our PlantNLRatlas dataset is complementary to RefPlantNLR, a collection of NLR genes which have been experimentally confirmed. The PlantNLRatlas should prove helpful for comparative investigations of NLRs across a range of plant groups, including understudied taxa. Finally, the PlantNLRatlas resource is intended to help the field move past a monolithic understanding of NLR structure and function.